Calisthenics: Epidemiology of Injury Patterns and Their Risk Factors - McDonald-Wedding L; Goodwin L; Preston A; McKay G; Williams C (Open Access Journal of Sports Medicine, 2023)
Laura McDonald-Wedding,1 Lauren Goodwin,2 Annabel Preston,3 Gaylene McKay,4 Cylie Williams3 1Austin Health, Heidelberg, VIC, 3078, Australia; 2Department of Health Sciences, School of Public Health and Preventive Medicine, Monash University, Alfred Medical Research and Education Precinct (AMREP), Melbourne, VIC, 3004, Australia; 3Department of Physiotherapy, School of Primary and Allied Health Care, Monash University, Frankston, VIC, 3199, Australia; 4Alphington Sports Medicine Exercise and Rehabilitation, Alphington, VIC, 3078, AustraliaCorrespondence: Laura McDonald-Wedding, Austin Health, 145 Studley Road, Heidelberg, Victoria, Australia, Tel +61 403 313 972, Email laura.mcdonaldwedding@gmail.comObjective: To quantify the prevalence and nature of injuries and their risk factors in calisthenics to, therefore, inform the practitioner what to expect from these athletes.Methods: This study was an online cross-sectional survey of calisthenics athletes. Data were collected online and the survey was distributed via social media over six months in 2020. The purpose-built survey consisted of demographic, training and loading questions. Participants were provided with an injury definition and reported their total number of injuries sustained during calisthenics including detailed information on three most significant injuries, along with mechanism of injury and risk factors. Multivariate regression analyses were used to determine objective factors associated with the number of injuries.Results: There were 543 participants describing 1104 injuries. Mean (standard deviation (SD)) injury prevalence was 4.5 (3.3) per person. Of these injuries, 820 (74.3%) required training modification or treatment. Participants missed a mean (SD) 3.4 (5.1) weeks of training and engaged in a mean (SD) 10.9 (9.1) health professional consultations. The most common injuries were upper leg (24.5%), ankle/foot (22.8%) and lumbar spine (19.3%), with the majority being sprains/strains in nature (56.3%). Mechanism of injury included elevated work (27.6%), overuse (38.0%) and specific calisthenics skills (38.9%) – such as lumbar (40.6%) and lower limb (40.3%) extension-based movements. Subjective risk factors included load (66.8%), preparation (55.9%) and environmental factors (21.0%). Objective risk factors associated with higher numbers of injuries included increased years of participation, left leg dominance, increased training hours (regardless of training type) and state team participation (p< 0.05).Conclusion: Practitioners need to be aware that calisthenics athletes demonstrate a high proportion of strain/sprain injuries involving the lower limb and lumbar spine with causative movements being extension-based. Addressing risk factors such as loading, preparation, asymmetry, and the environment related to these movements are important for the treating practitioner.Keywords: sport injury, injury epidemiology, calisthenics, dancing, gymnastics, ballet, risk factors, injury prevention